Cutting Edge: TCR Ligation Triggers Digital Activation of NF-κB - Kingeter, Lara M; Paul, Suman; Maynard, Sean K; Cartwright, Natalia G; Schaefer, Brian C (The Journal of immunology (1950), 2010)
TCR-mediated activation of the transcription factor NF-κB is required for T cell proliferation, survival, and effector differentiation. Although this pathway is the subject of intense study, it is not known whether TCR signaling to NF-κB is digital (switch-like) or analog in nature. Through analysis of the phosphorylation and degradation of IκBα and the nuclear translocation and phosphorylation of the NF-κB subunit RelA, we show that TCR-directed NF-κB activation is digital. Furthermore, digitization occurs well upstream of the IκB kinase complex, as protein kinase C θ translocation to the immunologic synapse and activation-associated aggregation of Bcl10 and Malt1 also demonstrate both digital behavior and high correlation with RelA nuclear translocation. Thus, similar to the TCR-to-MAPK signaling cascade, analog Ag inputs are converted to digital activation outputs to NF-κB at an early step downstream of TCR ligation.